Dukungan Keluarga Dengan Kepatuhan Minum Obat Pada Pasien Diabetes Melitus Tipe II Di Puskesmas X Jakarta Barat - Tutut Fatmafati; Ricky Riyanto Iksan (Akademi Keperawatan Yarsi Samarinda, 2026)
Diabetes Mellitus is a condition caused by the failure of the pancreas to produce insulin. Uncontrolled diabetes can cause hyperglycemia or increased blood sugar, which can damage various body systems. This study aims to determine the relationship between family support and medication adherence in Type II Diabetes Mellitus patients at Community Health Center X, West Jakarta. The research design uses quantitative research with a cross-sectional design. This study uses a purposive sampling technique with a sample size of 89 respondents. The instrument used is a questionnaire. The analysis used is univariate analysis and bivariate analysis using the chi-square test. Results Most respondents have high family support (58.4%) and good medication adherence (69.7%). Bivariate analysis showed a significant relationship between family support and medication adherence in patients with type 2 diabetes mellitus. Patients with high family support were 4.526 times more likely to have good medication adherence than those with low family support (OR = 4.526; 95% CI: 1.724–11.884; p = 0.003). Conclusion: There is a significant relationship between family support and medication adherence in patients with type 2 diabetes mellitus. The better the family support provided, the higher the patient's medication adherence, thus supporting the successful management of type 2 diabetes mellitus.